The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12888-017-1391-2
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, quantitative study of mental health act assessments in England following the 2007 amendments to the 1983 act: did the changes fulfill their promise?

Abstract: BackgroundIn 2008, the Mental Health Act (MHA) 2007 amendments to the MHA 1983 were implemented in England and Wales. The amendments were intended to remove perceived obstacles to the detention of high risk patients with personality disorders (PDs), sexual deviance and learning disabilities (LDs). The AMEND study aimed to test the hypothesis that the implementation of these changes would lead to an increase in numbers or proportions of patients with these conditions who would be assessed and detained under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…This is interesting from a UK perspective because one of the amendments to the Mental Health Act in 2007 was designed to make it easier to involuntarily admit people with personality disorder who were thought to be at high risk. 63 However, only one of the studies that included data on personality disorder in this review came from the UK, and this study was published before 2010. The studies included in this review do not describe how risk is assessed and reported in children and adolescents and how this might influence decisions about the legal status of admission.…”
Section: Discussionmentioning
confidence: 99%
“…This is interesting from a UK perspective because one of the amendments to the Mental Health Act in 2007 was designed to make it easier to involuntarily admit people with personality disorder who were thought to be at high risk. 63 However, only one of the studies that included data on personality disorder in this review came from the UK, and this study was published before 2010. The studies included in this review do not describe how risk is assessed and reported in children and adolescents and how this might influence decisions about the legal status of admission.…”
Section: Discussionmentioning
confidence: 99%
“…There has been significant legislation passed by the houses of UK parliament on both climate change and mental health as separate critical challenges. The Mental Health Act was passed in 2007 and the Climate Change Act was passed in 2008, with amendments such as Net Zero 2050 made more recently (22)(23)(24). However, it is unclear to what extent UK decision-makers are considering the intersections between these critical issues and whether discussions are framed with reference to synergistic policy solutions.…”
Section: The Importance Of Uk Parliament In This Issuementioning
confidence: 99%